School environment and obesity in adolescents from a Brazilian metropolis: cross-sectional study - Maíra Macário de Assis; Lucia Helena Almeida Gratão; Thales Philipe Rodrigues da Silva; Nayhanne Gomes Cordeiro; Ariene Silva do Carmo; Cristiane de Freitas Cunha; Tatiana Resende Prado Rangel de Oliveira; Luana Lara Rocha; Larissa Loures Mendes (BMC, 2022)
Abstract Background Childhood-juvenile obesity is a globally acknowledged public health issue. The school environment has been widely assessed because it is where adolescents stay longer during the day, and it may have impact on obesity. School became a crucial environment for obesity prevention in children and adolescents. The aim of the present study was to associate schools' internal environment factors and its surrounding areas with obesity in adolescents from a Brazilian metropolis. Methods Cross-sectional study based on data from the Study on Cardiovascular Risk in Adolescents. The sample comprised 2,530 adolescents in the age group 12-17 years, who were enrolled in public and private schools in Belo Horizonte City, Brazil. Obesity was the dependent variable based on the cut-off point score-z + 2 for body mass index based on age. School environment's independent variables were 'managerial dependence type', 'number of drinking fountains', 'school sports environment' and 'ready-to-eat food shops' around the school (within an 800 m buffer). Results Obesity prevailed in 7.21% in sample. The largest number of drinking fountains decrease by 9% the chances of obesity in adolescents enrolled in public and private schools; however, the second and third terciles recorded for the number of ready-to-eat food shops within the 800 m buffer around schools increased by 24% and 44% the chances of obesity, respectively. Conclusion School food environment aspects such as the number of operational drinking fountains and the availability of ready-to-eat food shops around the school were associated with obesity in adolescents from a Brazilian metropolis.